Organizaton of American relief in Europe, 1918-1919. Including negotiations leading up to the establishment of the office of director general of relief at Paris by the allied and associated powers. Documents selected abnd ed. by S.L. Bane and R. Haswell Lutz (University press etc., 1943)
With map, reg. and tabs.